Leadership for Rural School District Improvement: The Case of One Statewide Research Practice Partnership - Elizabeth Wargo; Kathleen Budge; Davin Carr Chellman; Kathryn Canfield-Davis (Journal of Research in Rural Education, 2021)
Research-practice partnerships (RPPs), where researchers and practitioners work in concert to address persistent problems of practice, provide promising mutualistic benefits in urban school settings. Drawing on an integrated framework, this case study explores the initial development of an RPP between six small and rural school districts and two universities, highlighting the complexities of leadership and rurality associated with this type of school improvement work. By using a rapid reconnaissance focus group approach, known as the Sondeos, the political landscape in each district emerged, with nuanced (and in many cases shifting) boundaries. This place-conscious adaptive method may be a promising tool to support rural education researchers and rural school leaders as they work together to actualize viable research-informed improvement. However, our findings illustrate that adaptive leadership capacity building may be a necessary element to sustain such work.